A nonlinear control in αβ reference frame for single-stage three-phase grid-connected photovoltaic systems with an LCL-filter - Madani, Zakariae El; Yahya, Abdelhafid; Malki, Zakaria El (Institute of Advanced Engineering and Science, 2024)
This paper presents a nonlinear control in the stationary αβ reference frame for single-stage three-phase grid-connected photovoltaic systems. The system under study consists of a photovoltaic generator (PVG), a three-phase inverter, and an LCL-filter on the grid side. The main control objectives are to extract the maximum power from the PVG and deliver that power into the grid with high-quality power i.e. unity power factor (UPF). In order to achieve these objectives, a nonlinear controller is designed by using backstepping technique. The performance of this controller is evaluated under standard and variable atmospheric conditions. Simulation results demonstrate that the proposed controller has successfully met all the specified objectives. This study highlights the potential of using the nonlinear control based on backstepping technique in photovoltaic systems with LCL-filters. The modeling and simulation of the complete system are carried out using MATLAB/Simulink environment.